2021
DOI: 10.3390/medicina57070666
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Ictal Cardiac Autonomic Changes in Patients with Frontal Lobe Epilepsy and Temporal Lobe Epilepsy by Ultra-Short-Term Heart Rate Variability Analysis

Abstract: Background and Objectives: Abnormal epileptic discharges in the brain can affect the central brain regions that regulate autonomic activity and produce cardiac symptoms, either at onset or during propagation of a seizure. These autonomic alterations are related to cardiorespiratory disturbances, such as sudden unexpected death in epilepsy. This study aims to investigate the differences in cardiac autonomic function between patients with temporal lobe epilepsy (TLE) and frontal lobe epilepsy (FLE) using ultra-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Regarding laterality, the study found that most HRV indices included statistical differences between the right and left sides during the ictal period. These results are consistent with those of previous studies [ 48 , 54 , 74 ], which also reported lateral differences in HRV indices in patients with TLE. Both normalized low-frequency (nLF) power and the LF/HF ratio exhibited substantial increases during the ictal interval, indicating higher sympathetic activity.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Regarding laterality, the study found that most HRV indices included statistical differences between the right and left sides during the ictal period. These results are consistent with those of previous studies [ 48 , 54 , 74 ], which also reported lateral differences in HRV indices in patients with TLE. Both normalized low-frequency (nLF) power and the LF/HF ratio exhibited substantial increases during the ictal interval, indicating higher sympathetic activity.…”
Section: Discussionsupporting
confidence: 94%
“…The CVI during the ictal interval showed significant differences between the two groups (z = 2.20, p = 0.028), while during the postictal interval, normalized HF and the LF/HF ratio differed significantly between the two groups (z = 3.05, p = 0.002; and z = −2.7, p = 0.007, respectively). This could be related to elevated parasympathetic (vagal) activity during the postictal period [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic dysfunction can manifest in individuals grappling with temporal lobe epilepsy or type 2 diabetes mellitus, even in the absence of neuropathy. Employing a 5-min assessment of HRV emerges as a pivotal technique for uncovering concealed cardiac autonomic neuropathy (CAN) [11,12]. The influence of seizures on the onset of cardiac autonomic neuropathy (CAN) has been implicated in instances of sudden unexpected death in epilepsy among those with the condition [5].…”
Section: Discussionmentioning
confidence: 99%